Methane emissions from pan‐Arctic lakes during the 21st century: An analysis with process‐based models of lake evolution and biogeochemistry. Issue 12 (30th December 2015) - Tan, Zeli; Zhuang, Qianlai
Abstract: The importance of methane emissions from pan‐Arctic lakes in the global carbon cycle has been suggested by recent studies. These studies indicated that climate change influences this methane source mainly in two ways: the warming of lake sediments and the evolution of thermokarst lakes. Few studies have been conducted to quantify the two impacts together in a unified modeling framework. Here we adapt a region‐specific lake evolution model to the pan‐Arctic scale and couple it with a lake methane biogeochemical model to quantify the change of this freshwater methane source in the 21st century. Our simulations show that the extent of thaw lakes will increase throughout the 21st century in the northern lowlands of the pan‐Arctic where the reworking of epigenetic ice in drained lake basins will continue. The projected methane emissions by 2100 are 28.3 ± 4.5 Tg CH4 yr −1 under a low warming scenario (Representative Concentration Pathways (RCPs) 2.6) and 32.7 ± 5.2 Tg CH4 yr −1 under a high warming scenario (RCP 8.5), which are about 2.5 and 2.9 times the simulated present‐day emissions. Most of the emitted methane originates from nonpermafrost carbon stock. For permafrost carbon, the methanogenesis will mineralize a cumulative amount of 3.4 ± 0.8 Pg C under RCP 2.6 and 3.9 ± 0.9 Pg C under RCP 8.5 from 2006 to 2099. The projected emissions could increase atmospheric methane concentrations by 55.0–69.3 ppb. This study further indicates that the warming of lake sediments dominates the increase of methane emissions from pan‐Arctic lakes in the future. Key Points: CH4 emissions from Arctic lakes will rise substantially in the 21st century Most of the emitted CH4 originates from nonpermafrost carbon stock The increased CH4 emissions will mainly be a consequence of lake sediments warming